Strategi Organisasi Siswa Intra Sekolah dalam Membentuk Karakter Kepemimpinan Siswa SMK PAB 8 Sampali - Tegar Jaya Putra; Muhammad Rifa'i (Universitas Negeri Malang, 2023)
Abstract. This research aims to determine the role of the Intra-School Student Organization (OSIS) in shaping the character of students at SMK PAB 8 Sampali. This research also aims to determine the challenges of OSIS in forming student character. The type of research is descriptive research using a qualitative approach. The subjects of this research are OSIS administrators, students who are OSIS administrators and students who are not OSIS administrators who are determined using purposive techniques. Meanwhile, data collection techniques use interview, observation and documentation techniques. The data analysis technique used is an inductive data analysis technique, with steps including data collection, data reduction, data display and drawing conclusions.The results of this research show the role of OSIS in shaping the character of students at SMK PAB 8 Sampali. The role of the OSIS in shaping student character: (1) as a forum, namely a place for students to work together to achieve goals, (2) as a driving force, namely to help the school carry out certain activities and (3) as a means of preventing students from deviating by participating in OSIS activities.Keywords: Strategy, OSIS, Leadership Abstrak. Penelitian ini bertujuan untuk mengetahui peranan Organisasi Siswa Intra Sekolah (OSIS) dalam membentuk karakter siswa SMK PAB 8 Sampali. Penelitian ini juga bertujuan untuk mengetahui hambatan OSIS dalam membentuk karakter siswa. Jenis penelitian adalah penelitian deskriptif dengan menggunakan pendekatan kualitatif.Subjek penelitian ini adalah pembina OSIS, siswa pengurus OSIS dan siswa bukan pengurus OSIS yang ditentukan dengan teknik purposive. Adapun teknik pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis data induktif, dengan langkah-langkah meliputi pengumpulan data, reduksi data, display data dan pengambilan kesimpulan. Hasil penelitian ini menunjukkan peranan OSISdalam membentuk karakter siswa SMK PAB 8 Sampali. Peranan OSIS dalam membentuk karakter siswa: (1) sebagai wadah yaitu tempat bagi siswa saling bekerja sama untuk mencapai tujuan, (2) sebagai penggerak yaitu untuk membantu sekolah menjalankan kegiatan tertentu dan (3) sebagai sarana menghindarkan siswa untuk berbuat menyimpang dengan mengikuti kegiatan OSIS.Kata Kunci: Strategy, OSIS, Kepemimpinan